SISTEM INFORMASI MANAJEMEN DESA (SIMANDE) BERBASIS WEB DI DESA TALAWI HILIE - Rizal Akhiar Ramadhan; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
ABSTRACTThe Village Management Information System is a system that produces information to support the management operations function and determine actions in the Village Government organization and Government on it. This system is designed and built based on the web to make it easier for relevant parties to interact with the system. The purpose of the design and construction of this system is to be able to realize orderly village government administration so as to produce the right information so that Village Governments and Governments at the top level can make decisions or policies that are also appropriate and to be able to shorten the time of administration by the public. The method of building this system begins by analyzing the system that is running and analyzing the system to be built. After analyzing the system, then designing the system using the Unified Modeling Languege modeling, MySQL Database Management System and built using the CodeIgniter Framework. The Village Management Information System was built based on observations made in Talawi Hilie Village, Talawi District, Sawahlunto City. With the construction of this system the Village Government can eliminate problems in the process of village administration, the community can save time in conducting village administration administration, and the Village Government and other relevant agencies can improve productivity and quality of work. Keywords: Information System, UML, MySql, codeIgniter.